Comparative Evaluation of Lamina Cribrosa Anatomical Parameters with Retinal Nerve Fiber Layer Thickness Defects In Primary Open-angle Glaucoma Cases And Controls - Ayesha Saba Naz; Aisha Qamar; Ambreen Surti; Sehrish Shafique; Yasmeen Mahar; Yawar Zaman; Nasim Marvi (Gandhara University, 2023)
OBJECTIVES To assess the lamina cribrosa (LC) anterior lamina cribrosa depth (ALCD), lamina cribrosa thickness (LCT) and retinal nerve fiber layer thickness (RNFLT) in primary open-angle glaucoma (POAG) cases and age-matched controls and to compare these anatomical variables among POAG cases and age-matched controls. METHODOLOGY The case-control study was researched at Al-Ain Eye Institute, Karachi, in four month's duration (November 2018 till February 2019). Expert eye specialist recruited 57 POAG cases and 46 age-matched healthy controls. Observation of intraocular pressure (IOP) and open angle was done using Goldmann tonometry and Slit-lamp biomicroscopy with stereoscopic ophthalmoscopy respectively. Visual field parameters of mean deviation (MD) and pattern standard deviation (PSD) measured using Humphrey Field Analyzer. Highly sensitive spectral domain ocular coherence tomography with enhanced depth imaging (EDI-OCT) was used to determine ALCD, LCT and RNFLT. RESULTS Statistically significant results were produced by RNFLT defects when it is compared in groups of mild with moderate cases of POAG (P-value 0.037). ALCD and LCT did display an association with RNFLT defects but did not produced statistically significant results. CONCLUSION Assessments of ALCD and LCT can provide important prognostic evidence about RNFLT and can assist in future planning of mild and moderate cases suffering from POAG.